The Mongolian Script in the Baikal region at the Present Stage: a Course for Revitalization? - Innokenty G. Aktamov; Nadezhda B. Badmatsyrenova (Монголоведение)
This paper aims to provide an analysis of the development of the Mongolian script in the sociocultural context of the Baikal region in modern times. The main purpose of this article is to characterize the key trends in society from the point of view of sociolinguistic processes. Materials and methods. The research is based on a thorough examination of official data from the Government of the Republic of Buryatia, government departments of the Irkutsk region and Transbaikal region, as well as publications in the media and field materials gathered through an expert survey of heads of educational centers and language activists. The authors have adopted a systematic approach and applied a range of general scientific and special methods, including comparative historical and statistical methods, to conduct this study. Results and conclusions. It has been revealed that the Mongolian script has significant role in performing various socio-cultural functions. Mongolian script has gained widespread popularity in the form of calligraphy in the Baikal region. Furthermore, the language is deeply embedded with ethno cultural symbolism, making it a valuable source for the development of the Buryat language and culture as a whole. There is a growing interest in analyzing the language situation in Mongolia and the Inner Mongolia Autonomous Region of the People’s Republic of China, particularly in terms of the implementation of state language policy in perspective. The status and functional role of Mongolian script in these regions are of utmost importance in understanding its impact on the overall language landscape.